Does use of power affects relationship's social satisfaction in manufacturer-dealers relationship? - Hussin, Zolkafli; Perumal, Selvan; Mohd Noor, Nor Azila; Othman, Abdul Rahim (2014)
Managing the channel relationship is a key concern in manufacturer-dealer relationship.This study investigates the automobile dealers’ relationship satisfaction and perceptions on supplier’s use of power.Despite the assumption that relationship satisfaction contributes to buyer-supplier relationship, previous researches had concentrated more on understanding factors affecting overall relationship satisfaction.Hence, less attention was given to understand the effect on specific of relationship satisfaction i.e. social relationship satisfaction.Using a survey method, this study described the uses of power as antecedents of social relationship satisfaction among 107 car dealers in Malaysia. Results showed that the significant effect of non-coercive power on the relationship social satisfaction.